Family Support for People Living with AIDS in North Halmahera District - Blandina, Olivia Asih; Manisa, Juan Charlos (International Journal of Multidisciplinary Approach Research and Science, 2024)
People with HIV/AIDS are people who have been positively infected with HIV/AIDS. Comprehensive family support, namely informational, emotional, rewarding and instrumental support can have a major impact on individuals to live a sustainable life. Family support for people with HIV/AIDS (PLWHA) in North Halmahera Regency shows that each respondent has different perceptions in terms of providing support to people with HIV/AIDS (PLWHA) stating that in providing 4 family support, namely informational support, emotional support, appreciation, and instrumental. Information support, respondents who stated that they provided informational support to people with HIV/AIDS, namely respondents 1, 4 and respondents 2, 3 stated that they did not provide or receive information support from their families. Emotional support, all respondents stated that they provide emotional support to people living with HIV/AIDS (PLWHA). Appreciation support, respondents who give awards to PLWHA in the form of appreciation support, namely respondents 1, and 4, while respondents 2 and 3, do not receive appreciation support so that respondent 2 experiences rejection in the social environment. While the instrumental support, instrumental support in this study, it can be concluded that respondents 1, 3, 4 provide instrumental support as a whole while respondent 2 only gets partial instrumental support.